Stureholm - Brunnström, Åse (2005)
Stureholm Manor and garden is a relatively young farming unit on clay soil in the north western part of Skåne, a province in Southern Sweden. Since the middle of the 19th century the landscape has been actively cultivated and has been transformed from oak forrest into farmingland of high efficiency. The industrial era during the 19th and 20th centuries meant new posssibilites for cultivation of these clay soils. With equipment like steam ploughs and the possibility to obtain fertilizers, the harvest increased considerably. This increased prosperity provided estate Stureholm with a beatuiful corps de logi, a manor. The trends prevailing in Europe around the turn of the century 1800-1900 against the growing industrialism, was turned into a artisan movement known as Arts and Craft. The Swedish followers idealized our Swedish history and they took the turn of a national romantic movement that later turned into neoclassicism. The neoclassical movements had strong support among Swedish garden architects such as the Crown Princess Margareta and Rudolf Abelin among others. They have both founded their own renowned gardens in Skåne, Sofiero in Helsingborg and Norrviken in Båstad, both excellent examples of neoclassicism. National romantic features are demonstrated at Stureholm Manor and gardens with it's pergola. Two productive personalites from Helsingborg, architect Ola Andersson and the town gardenarchitect Oscar Landsberg were employed to actualize the dreams of a paradise that Sture and Alice Brunnström wished to create at Stureholm. Their Manor was completed 1912 and in 1918 the formal garden with its pergola was laid out. The garden of the Manor should not only be for pleasure. Very early on big plans were made for fruit orchards and a greenhouse. Hazelbushes were planted, beds for asparagus dug. A peachhouse, garden beds for growing vegetables and berrys were all needed along with somewhere to grow annuals (summerflowers). It was quite a large garden and to make it all possible a headgardener was employed. His responsibility being to manage and maintain the garden and to secure harvest for the Manors family and their guests all the months of the year, may it be fruit or flowers. Not only a productive garden but a garden for enjoyment for both the family, their children and of course their many guests, has been undergoing many natural changes during the almost one hundred years that have now passed. The garden that originally was laid out is still there but much of it's original living material has not survived our Swedish climat. The gardens formal architecture, the pergola, needs to be restored. Descisions for the future have been taken and a general plan has been drafted, which also include plans that should give the garden a renewed beauty. Other plans also include major developments for the estate, since pigglet production stopped in 2002. Since a few of decades ago the Manor regretfully no longer employs a headgardener. The orchard with apple- and peartrees has became overaged and most of the trees are now gone. Subsequently the buildings are also in need of restoration. The old orchards are now history and in their place an arboretum is in the planning. Hopefully like an english landscape park with paths crossing through the lawn, new sightlines and new places to sit, this hopefully will give more opportunity to enjoy the garden, the park and the arcitechture, that already so well interacts with the old oak forest.